2022
DOI: 10.3390/ph15060762
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Role of Pilocarpine on the Management of Xerostomia and the Importance of the Topical Administration Systems Development

Abstract: Xerostomia is linked to an increased risk of dental caries, oral fungal infections, and speaking/swallowing difficulties, factors that may significantly degrade patients’ life, socially- or emotionally-wise. Consequently, there is an increasing interest in developing management approaches for confronting this oral condition, at which pilocarpine, a parasympathomimetic agent, plays a vital role. Although the therapeutic effects of orally administrated pilocarpine on the salivary gland flow and the symptoms of x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 84 publications
0
14
0
Order By: Relevance
“…This not only reduces the patients' living quality but also seriously affects the course of radiotherapy 4,5 . At present, the main treatment for irradiation‐induced salivary gland damage is palliative treatment including artificial saliva, saliva substitutes, saliva stimulating agents (pilocarpine), acupuncture therapy, electrostimulation and hyperbaric oxygen therapy 6 . However, all these methods are only effective for a short time and cannot restore damaged salivary gland tissue; thus, the therapeutic effect of these methods is not satisfactory 7 .…”
Section: Introductionmentioning
confidence: 99%
“…This not only reduces the patients' living quality but also seriously affects the course of radiotherapy 4,5 . At present, the main treatment for irradiation‐induced salivary gland damage is palliative treatment including artificial saliva, saliva substitutes, saliva stimulating agents (pilocarpine), acupuncture therapy, electrostimulation and hyperbaric oxygen therapy 6 . However, all these methods are only effective for a short time and cannot restore damaged salivary gland tissue; thus, the therapeutic effect of these methods is not satisfactory 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors may cause xerostomia, such as dehydration, aging, habits such as breathing through the mouth, smoking, alcohol, excessive caffeine consumption, systemic diseases, autoimmune diseases, xerogenic drugs, psychological conditions, head and neck radiotherapy, and malnutrition. 14 , 20–27 Autoimmune diseases can cause xerostomia, such as psoriasis in this case. Determining the etiology of xerostomia allows for an appropriate diagnosis and early intervention.…”
Section: Introductionmentioning
confidence: 90%
“…The emergence of xerostomia can be attributed to an array of systemic or localized causative factors [ 6 , 7 ], such as extensive medication usage, head and neck radiation therapy, and systemic pathologies, including diabetes mellitus, sarcoidosis, systemic lupus erythematosus, and the autoimmune disorder known as Sjögren’s syndrome [ 8 , 9 , 10 , 11 ]. Upon scrutinizing the existing literature, it is evident that the prevalence of xerostomia in the general population exhibits considerable variation, with reported incidences among adults spanning from 5.5% to 46% [ 12 , 13 ].…”
Section: Generalmentioning
confidence: 99%
“…As the most prevalent medication for the treatment of Sjögren’s syndrome and relief of radiation-induced xerostomia symptoms, pilocarpine has gained approval from the U.S. Food and Drug Administration (FDA). Numerous studies have demonstrated the efficacy of administering pilocarpine in managing xerostomia, which can be divided into systemic and topical administration [ 12 ]. Pilocarpine stimulates natural salivation by binding to the muscarinic acetylcholine receptor 3 (M3R) located in the acinus cells of the salivary glands.…”
Section: Natural Products Used For the Treatment Of Xerostomiamentioning
confidence: 99%